TUMBUH KEMBANG ANAK USIA 0-5 TAHUN - Merita Merita (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
Some of the effects of child development that are not in accordance with their age can inhibit brain development. Therefore, the purpose of this service is to carry out counseling on growth and development in children under five age. This activity was held from September 2018 to January 2019, at the Sukasari Posyandu, Sarolangun District. Sasaran is a mother who has children aged 0-5 years. This activity consisted of giving counseling with power point media, leaflets, posters, and pre-post test questions and anthropometric measurements of toddlers. The output of this service activity are: (1) Media leaflets and posters of child development and; (2) Mother's behavior in monitoring child growth and development. The results of the activity showed that participants were able to answer questions related to growth material in children aged 0-5 years in the post-test stage, ie correct answers of ≥ 80%. Participants are also able to understand the material about child development related to good consumption patterns through discussion. Based on this activity, it is necessary to collaborate with health workers and cadres to motivate children under five to routinely monitor the growth of children under five to posyandu or the nearest health care facility.